The Effect of Increasing the Body’s Core Temperature and Improving Blood Flow by Using Far-Infrared Rays Emitted from Functional Loess Bio-Balls - Yong-Il Shin; Min-Seok Kim; Yeong-Ae Yang; Gye-Rok Jeon; Jae-Ho Kim; Yeon-Jin Choi; Woo-Cheol Choi; Jae-Hyung Kim (Biomedicines)
Background: Low-energy far-infrared rays (FIRs) are widely used in the treatment of wounds, lymphedema, and various vascular diseases, and various types of products that emit infrared rays are being used at home for patients with blood flow-related diseases without experimental evidence. Methods: Blood flow and epidermal temperature were measured while applying conductive heat and FIRs via an electric mat (non-intervention) or a loess bio-ball mat (intervention). Results: In the control group (n = 30), there was a minimal change in blood flow and epidermal temperature in the right and left middle fingers (LMF, RMF) as the mat temperature gradually increased. In the experimental group (n = 30), when the mat temperature increased from 25 °C to 50 °C, the blood flow increased by 39.80% in the LMF and by 41.83% in the RMF. In addition, the epidermal temperature increased by 8.78% in the LMF and by 8.44% in the RMF. Conclusions: The FIRs emitted from loess bio-balls can be applied to alleviate symptoms not only in patients with blood flow problems in medical settings but also in people who complain of discomfort due to blood flow disorders or cold hands and feet during their daily life and sleep.